The Cold War Community of Love and Scorn: Robert Duncan, The New American Poetry, and the Lavender Scare - Stephan Delbos (Sillages Critiques)
Robert Duncan’s significance for anglophone poetry after World War II is indisputable. But Duncan communicated with his milieu – both supportively and antagonistically – in unpublished letters as much as in his published poetry and essays. This essay centers around an exchange between Robert Duncan and editor Donald Allen in 1960, just after the publication of The New American Poetry. In one important letter, Allen suggests that “the community of love” was the central unifying feature of the poetry in the anthology. This inspired a long reply from Duncan, detailing his feelings about specific poets while describing the ability to experience and write about sexuality and romance as a significant difference between the poets of Allen’s anthology and the so-called academic poets of the period. Clarifying Duncan’s role in the development of Allen’s anthology, this essay highlights the political and social repercussions of The New American Poetry as well as the vulnerability Duncan felt as a homosexual poet during a period known as the Lavender Scare.